ARTFL-FRANTEXT
ARTFL-FRANTEXT is the main ARTFL Database, comprising more than 3,600 French-language texts, 215 million words and 675,000 unique word forms. The corpus contains texts ranging from classic works of French literature to various kinds of non-fiction prose and technical writing. The eighteenth, nineteenth and twentieth centuries are about equally represented, with a smaller selection of seventeenth century texts as well as some medieval and Renaissance texts. Genres include novels, verse, theater, journalism, essays, correspondence, and treatises. Subjects include literary criticism, biology, history, economics, and philosophy. In most cases standard scholarly editions were used in converting the text into machine-readable form, and the data contain page references to these editions.